2020
DOI: 10.1101/2020.05.08.084103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AI334 and AQ806 antibodies recognize the spike S protein from SARS-CoV-2 by ELISA

Abstract: We tested 10 recombinant antibodies directed against the spike S protein from SARS-CoV-1. Among them, antibodies AI334 and AQ806 detect by ELISA the spike S protein from SARS-CoV-2.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Indeed, we did not observe a strong response to linear peptides in the RBD. A control experiment with AI334/CR3022 antibody [25, 70] showed only weak binding to 367-378 peptide sequence of the RBD.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we did not observe a strong response to linear peptides in the RBD. A control experiment with AI334/CR3022 antibody [25, 70] showed only weak binding to 367-378 peptide sequence of the RBD.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we did not observe a strong response to linear peptides in the RBD. A control experiment with AI334/CR3022 antibody [25,71] showed only weak binding to 367-378 peptide sequence of the RBD.…”
Section: Plos Onementioning
confidence: 93%
“…1). AI334 was used as a positive control (Hammel et al, 2020); AS273 showed no specific binding, most probably due to the fact that this antibody is poorly produced ( Table 1, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%